PENGARUH VOLUME MODAL USAHA DAN STRATEGI PEMASARAN TERHADAP PERKEMBANGAN UMKM MELALUI SKILL MANAJERIAL DI DESA SRIKATON KABUPATEN PRINGSEWU - Dwi Suryanto; Erlina Rufaidah; Yon Rizal (Economic Education and Entrepreneurship Journal, 2019)
The Effect Of Business Capital Volume And Marketing Strategy Towards Development Of Umkm Through Skills Managerial In Srikaton Village Pringsewu District. The purpose of this study was to determine the effect of business capital volume and marketing strategies on the development of UMKM through managerial skills in Srikaton Village, Pringsewu Regency. The method used in this research is descriptive verification with ex post facto and survey approaches. The sample used in this study is that all UMKM in the village of Srikaton are 37 UMKM. The data collected is processed using path analysis. The analysis shows that there is an influence of business capital volume and marketing strategy on the development of UMKM through managerial skills in Srikaton Village, Pringsewu Regency, both simultaneously and partially.